The Use of Charades Games in Teaching Vocabulary to the Junior High School Students - Muhammad Fauzi Bafadal; Humaira Humaira (Muhammadiyah University of Mataram, 2018)
Vocabulary is a knowledge of words and word meanings. To increase the student’s vocabulary, the writer chosen game. A game is an alternative way to teach. One of the alternative games is a charades game. So, based on it the aim of this study is to investigate the effect of charades game toward student’s vocabulary. This study was conducted at the first-grade students of SMPN 18 Mataram in academic year 2017/2018. This study used a quasi-experimental design that is used pre-test and post-test control group design. The population of study involved 40 students from two classes SMPN 18 Mataram in academic year 2017/2018. The writer took all of the students as a sample, and they are 20 students belong to the experimental group and 20 students in the control group. In this study, the writer used the vocabulary test consists of 20 items multiple choice covered with the indicator of vocabulary consist of spelling, pronunciation, and meaning. The result of this study, the students could understand spelling, pronunciation, and meaning and they could answer the test vocabulary easily through charades game. In this data, pre-test, and post-test as the research technique of data collection, then followed by analyzing the data using the t-test formula. The level of significance is at 0, 05%, t-test = 2,99 and t-table= 2,02, Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It means that there was a significant difference between the student's pre-test and post-test scores. Thus, the writer concludes that the charades game on the student’s vocabulary affects.